Social Support for Adolescent Resilience in Dealing With Conflicts in Divorced Parents - Muhadir Muhammad; Herman Nirwana; Marjohan Marjohan (Universitas Negeri Padang, 2019)
This research aims to determine social support for adolescent resilience in dealing with conflict in divorced parental environments that includes phase dimensions, and resilience strategies. This article is based on research using a qualitative method of case study type. Research subjects numbered 3 teenagers with the criteria of having divorced parents alive. Data collection techniques used in the form of in-depth interviews and observation. The data analysis technique used by researchers is guided by the Miles & Huberman model. The results of the analysis of research data indicate that the resilience phase that is passed by adolescents whose parents divorced live differently from each other. This is influenced by social support factors obtained by adolescents in facing life's challenges. The different phases through which each subject will also distinguish the resilience strategies used by each subject to survive in the face of conflict in the environment of divorced parents.